Minimal fixation suffices for supine isokinetic knee extension: A kinetic and 3D kinematic analysis - Alt, T.; Richert, M.; Schwarz, Y. M.; Knicker, A. J.; Strüder, H. K. (Isokinetics and Exercise Science, 2016)
Isokinetic tests are used to measure muscular performance, especially strength. A proper axis alignment ensures high measuring accuracy. OBJECTIVE: The effects of fixation (minimal vs. maximal), contraction mode (concentric vs. eccentric) and angular velocity (30 vs. 150°/s) on the kinetics and 3D kinematics of supine knee extensions need further investigation. METHODS: Eighteen healthy male participants (22.1 y, 1.83 m, 76.0 kg) performed maximal unilateral contractions with minimal (hand grips only) and maximal (grips, knee, hip and trunk straps) fixation. RESULTS: Peak moments (+5%) and contractional work (+4%) significantly increased at minimal fixation. Maximal fixation improved sagittal axis alignment in terms of the trajectory length of the lateral femoral epicondyle (-34%) and the mean distance to trajectory centre (-19%). Both kinematic parameters showed highly significant interactions of fixation, contraction mode and angular velocity (p< 0.01). Initial axis alignment in relaxed muscular state caused an antero-cranial shift (0.8 and 2.4 cm) of the lateral femoral epicondyle as well as mean roll and yaw angle tilts of each 2.3° each. CONCLUSIONS: For supine isokinetic knee extensions, hand grips suffice as fixation to obtain accurate kinematic and kinetic results. If fixation is tight, the force output will decrease. To minimise misalignment, lining up should be executed when muscles are contracting isometrically.